TALENT MANAGEMENT IN THE CAREER COACHING STYLE USING A METAPROGRAM APPROACH - N. M. Tverdola (Вестник университета)
There is a point of view that it is already impossible to bring new ideas into talent management. The current practice has been considered in the article and also an alternative approach that can increase the quality of training of talent pool to a higher level has been presented . A new strategy for integrating career coaching and a metaprogram approach into the system of talent pool management, as well as a different starting point for work with it, have been proposed. The prospects and potential of candidates for company vacancies to be included in the personnel reserve are already assessed at the recruitment stage. Specific steps have been listed. The author’s definition of the term “career coaching” has been given.